2022
DOI: 10.4251/wjgo.v14.i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for response to immune checkpoint inhibitors in gastrointestinal cancers

Abstract: Gastrointestinal (GI) cancers account for a large proportion of cancer deaths worldwide and pose a major public health challenge. Immunotherapy is considered to be one of the prominent and successful approaches in cancer treatment in recent years. Among them, immune checkpoint inhibitor (ICI) therapy, has received widespread attention, and many clinical findings support the feasibility of ICIs, with sustained responses and significantly prolonged lifespan observed in a wide range of tumors. However, patients t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 115 publications
0
3
0
1
Order By: Relevance
“…Several scoring systems such as CPS and TPS have been established, however, the ideal scoring system is not yet revealed, and biomarkers to select individual ICIs remain unknown. Recently, novel biomarkers to predict the treatment response and prognosis after ICI therapy such as tumor-genome biomarkers, tumor immune microenvironment-related biomarkers, and liquid biopsy biomarkers have been reported in several gastrointestinal diseases[ 24 ], and the combination of several biomarkers is noteworthy. Future prospective trials and the development of novel technologies, such as single-cell analysis and machine learning, may lead to the development of optimal ICI biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Several scoring systems such as CPS and TPS have been established, however, the ideal scoring system is not yet revealed, and biomarkers to select individual ICIs remain unknown. Recently, novel biomarkers to predict the treatment response and prognosis after ICI therapy such as tumor-genome biomarkers, tumor immune microenvironment-related biomarkers, and liquid biopsy biomarkers have been reported in several gastrointestinal diseases[ 24 ], and the combination of several biomarkers is noteworthy. Future prospective trials and the development of novel technologies, such as single-cell analysis and machine learning, may lead to the development of optimal ICI biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation‐induced ferroptosis is favourable for cancer therapy, while the products of cells undergoing ferroptosis can act as immunogen to induce immune cell infiltration 22 . Previous studies indicated that ICI based on the data obtaining from high‐throughput sequencing is helpful for the precise treatment of HCC 23,24 . Herein, therefore, we first aimed to explore novel biomarker associated with inflammation and ferroptosis in HCC tissues, and its effect on guiding immunotherapy via analysing high‐throughput sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Previous studies indicated that ICI based on the data obtaining from high‐throughput sequencing is helpful for the precise treatment of HCC. 23 , 24 Herein, therefore, we first aimed to explore novel biomarker associated with inflammation and ferroptosis in HCC tissues, and its effect on guiding immunotherapy via analysing high‐throughput sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…Внедрение ингибиторов контрольных иммунных точек в рутинную клиническую практику позволило сохранить качество жизни пациентов, и в ряде исследований улучшить отдаленные результаты лечения в определенных группах пациентов с мРЖ [2, [10][11][12]. Так, наиболее хорошо изученными предикторами ответа на иммунотерапию являются уровень экспрессии PD-L CPS и наличие микросателлитной нестабильности (MSI) [13,14]. Стандартом первой линии мРЖ является комбинация ниволумаба или пембролизумаба с оксалиплатин-содержащими режимами при уровне PD-L CPS ≥5 и ≥10 соответственно [2,15].…”
unclassified